Speciation by genome duplication: Repeated origins and genomic composition of the recently formed allopolyploid species Mimulus peregrinus. (27th May 2015) - Vallejo‐Marín, Mario; Buggs, Richard J. A.; Cooley, Arielle M.; Puzey, Joshua R.
<x xml:space="preserve">Abstract</x> Whole genome duplication (polyploidization) is a mechanism of "instantaneous" species formation that has played a major role in the evolutionary history of plants. Much of what we know about the early evolution of polyploids is based upon studies of a handful of recently formed species. A new polyploid hybrid (allopolyploid) species Mimulus peregrinus, formed within the last 140 years, was recently discovered on the Scottish mainland and corroborated by chromosome counts. Here, using targeted, high‐depth sequencing of 1200 genic regions, we confirm the parental origins of this new species from M. x robertsii, a sterile triploid hybrid between the two introduced species M. guttatus and M. luteus that are naturalized and widespread in the United Kingdom. We also report a new population of M. peregrinus on the Orkney Islands and demonstrate that populations on the Scottish mainland and Orkney Islands arose independently via genome duplication from local populations of M. x robertsii. Our data raise the possibility that some alleles are already being lost in the evolving M. peregrinus genomes. The recent origins of a new species of the ecological model genus Mimulus via allopolyploidization provide a powerful opportunity to explore the early stages of hybridization and genome duplication in naturally evolved lineages.